Arctic surface Urban Heat Island (UHI), MODIS Land Surface Temperature (LST) data, 2000-2016. ... - Miles, Victoria (NSF Arctic Data Center, 2020)
This data set is comprised of two image maps and one data file. The data file contains Land Surface Temperature (LST) derived from Moderate Resolution Imaging Spectroradiometer (MODIS) data, and surface Urban Heat Island (UHI) data calculated based on LST data for 118 arctic and sub-arctic urban areas, 2000-2016. Seasonally and temporally averaged urban LST and surface UHI time series are provided in the data archive. These data were analyzed for cities in northern West Siberia (Miles and Esau, 2017) and 57 cities in northern Fennoscandia (Miles and Esau, 2020). This data set was produced in the project 'Collaborative Research: HIARC: Anthropogenic Heat Islands in the Arctic: Windows to the Future of the Regional Climates, Ecosystems, and Societies'. The international HIARC project was performed within the Belmont Forum Collaboration Research Action (CRA) on 'Arctic Observing and Research for Sustainability', with funding from the Research Council of Norway, NSF, and the Russian Foundation for Basic Research. ...